Identification of Coffee Berry Borer from Similar Bark Beetles in Southeast Asia and Oceania - Andrew Johnson; Gabriel LeMay; Jiri Hulcr (EDIS)
This guide aims to assist in the accurate identification of a highly damaging pest, the coffee berry borer Hypothenemus hampei. Key morphological characters are noted which may distinguish it from similar species found in coffee berries and coffee berry borer traps. Similar genera are also distinguished, though the guide does not provide identification of these genera to species. Useful to both professionals and non-professionals, the guide provides a glossary of anatomical terms used as well as annotated figures of specimens. It is hoped that increased accuracy in identification of coffee berry borer will assist in efforts to limit the spread of the beetle in coffee growing regions around the world.